2009
DOI: 10.1038/nrc2763
|View full text |Cite
|
Sign up to set email alerts
|

Awakening guardian angels: drugging the p53 pathway

Abstract: Currently, around 11 million people are living with a tumour that contains an inactivating mutation of TP53 (the human gene that encodes p53) and another 11 million have tumours in which the p53 pathway is partially abrogated through the inactivation of other signalling or effector components. The p53 pathway is therefore a prime target for new cancer drug development, and several original approaches to drug discovery that could have wide applications to drug development are being used. In one approach, molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
808
0
8

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 818 publications
(822 citation statements)
references
References 140 publications
6
808
0
8
Order By: Relevance
“…6−8 In tumor cells with wild-type p53 (∼50%), reactivation of the p53 pathway by inhibition of MDM2 with small molecules has been considered as potentially an attractive novel therapeutic approach for cancer treatment. 9,10 Currently, several smallmolecule MDM2 inhibitors including RG7112 and RG7388 ( Figure 1) are undergoing clinical evaluations. 11−14 To maximize the chance of success in the clinic and derisk any potential idiopathic toxicity associated with specific chemotypes, continued research efforts are required to expand chemodiversity and identify potent and selective MDM2 antagonists with desirable in vitro ADMET and in vivo pharmacokinetic properties.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…6−8 In tumor cells with wild-type p53 (∼50%), reactivation of the p53 pathway by inhibition of MDM2 with small molecules has been considered as potentially an attractive novel therapeutic approach for cancer treatment. 9,10 Currently, several smallmolecule MDM2 inhibitors including RG7112 and RG7388 ( Figure 1) are undergoing clinical evaluations. 11−14 To maximize the chance of success in the clinic and derisk any potential idiopathic toxicity associated with specific chemotypes, continued research efforts are required to expand chemodiversity and identify potent and selective MDM2 antagonists with desirable in vitro ADMET and in vivo pharmacokinetic properties.…”
Section: * S Supporting Informationmentioning
confidence: 99%
“…Whereas inhibition of binding of MDM2 to p53 has successfully been achieved by several small molecules [85], no such specific molecules have been reported for MDMX. However, to take full advantage of the strategy to stabilize p53 function, MDM2 and MDMX need to be targeted [86].…”
Section: Ro2443mentioning
confidence: 99%
“…Those studies suggested that the reactivation of the p53 pathway in tumors has the potential to reduce tumor growth either in combination with other therapies or alone. Therefore, there is a growing interest in understanding the mechanisms of p53 inactivation and the therapeutic possibilities of reactivating dysfunctional p53 in cancers in order to halt tumor growth (Brown et al, 2009). In this review, we will focus on the role of homeodomain-interacting protein kinase-2 (HIPK2) in p53 activation.…”
Section: Introductionmentioning
confidence: 99%